(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Industrialization, population explosion, or changing lifestyles have led in the creation of non degradable contaminants harming the environment and human health. Biological methods employing microorganisms are gaining significance as an eco-friendly and cost-effective alternative to reduce the pollution burden. Microorganisms can live in a diverse environment and generate metabolites that may breakdown and convert toxins making it possible to resuscitate polluted areas naturally. Natural microbiomes have also been exploited in a variety of bioremediation approaches. New tools for studying bacterial activity in polluted or bioremediated sites have been developed as a result of recent breakthroughs in molecular bacterial communities. Such investigations provide information that aids in the evaluation of bioremediation effectiveness or the creation of techniques to speed up bioremediation.